2015
DOI: 10.1371/journal.pone.0125702
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Uncovers SNPs and Alternative Splicing Events in Asian Lotus (Nelumbo nucifera)

Abstract: RNA-Seq is an efficient way to comprehensively identify single nucleotide polymorphisms (SNPs) and alternative splicing (AS) events from the expressed genes. In this study, we conducted transcriptome sequencing of four Asian lotus (Nelumbo nucifera) cultivars using Illumina HiSeq2000 platform to identify SNPs and AS events in lotus. A total of 505 million pair-end RNA-Seq reads were generated from four cultivars, of which 86% were mapped to the lotus reference genome. Using the four sets of data together, a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…With the development of sequencing technologies, great success has been achieved in genome sequencing. Recently, the sacred lotus whole genome was sequenced ( Ming et al, 2013 ), which has provided ample information for the analysis of the transcriptome and proteome of this species ( Deng et al, 2015 ; Yang et al, 2015a , b ; Liu et al, 2016 ). Moro et al (2015b) profiled the endosperm proteome of mature lotus seed and they also compared the proteome profiles of the immature and mature seed endosperm.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of sequencing technologies, great success has been achieved in genome sequencing. Recently, the sacred lotus whole genome was sequenced ( Ming et al, 2013 ), which has provided ample information for the analysis of the transcriptome and proteome of this species ( Deng et al, 2015 ; Yang et al, 2015a , b ; Liu et al, 2016 ). Moro et al (2015b) profiled the endosperm proteome of mature lotus seed and they also compared the proteome profiles of the immature and mature seed endosperm.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a total of 3,180,059 SNPs, and 328,251 InDels were identified in the N . nucifera genome, which was much higher than that detected from the transcripts [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sacred lotus ( Nelumbo nucifera Gaertn.) (2 x = 2 n = 16), an aquatic perennial plant in the family Nelumbonaceae, has been cultivated as an ornamental or vegetable plant for more than 7000 yr throughout Asia ( Hu et al, 2012 ;Yang et al, 2015 ). Microsatellite (simple sequence repeat [SSR]) markers are sensitive tools for evaluating genetic diversity, population genetic structure, and intraspecifi c variation.…”
Section: Ap Applicati Tions Ons In In Pl Plant T Scien Sciences Cesmentioning
confidence: 99%